Analysing the relationship between tone and melody in Chaozhou songs. Issue 4 (8th August 2021) - Zhang, Xi; Cross, Ian
Abstract : This paper uses corpus analysis to explore relationships between tone and melody in folk and contemporary songs in Chaozhou, a Chinese dialect with eight lexical tones and a wealth of tone sandhi. Results suggest that: (1) there is a high degree of correspondence between tone and melody in Chaozhou song; (2) tone sandhi influences tone-melody correspondence; (3) tones realised in context can be categorised into high-, mid-, and low-pitch groups according to the tone-pitch extreme rather than final pitch; (4) when single tones are performed melismatically across groups of notes, relationships between initial notes of successive groups shapes tone-melody matching.